Associations of Polygenic Risk Score for Late-Onset Alzheimer's Disease With Biomarkers - Li, Qiaojun; Lv, Xingping; Jin, Fei; Liao, Kun; Gao, Liyuan; Xu, Jiayuan (Frontiers in Aging Neuroscience, 2022)
Late onset Alzheimer’s disease (LOAD) is a common irreversible neurodegenerative disease with heterogeneous genetic characteristics. Identifying biological biomarkers with the potential to predict the conversion from normal controls to LOAD is clinically important for early interventions of LOAD and clinical treatment. Polygenic risk score for LOAD (AD-PRS), have been reported the potential possibility for reliably identifying individuals with risk of developing LOAD recently. To investigate the external phenotypes changes resulting from LOAD and underlying etiology, we summarize the comprehensive associations of AD-PRS with multiple biomarkers, including neuroimaging, cerebrospinal fluid and plasma biomarkers, cardiovascular risk factors, cognitive behavior and mental health. This systematic review is helpful to improve the understanding of biomarkers with potential predictive value for LOAD and further optimize the prediction and accurate treatment of LOAD.